Scale Discourse and Dimensions of Social Life - Carr, E. Summerson (University of California Press, 2016)
Wherever we turn, we see diverse things scaled for us, from cities to economies, from history to love. We know scale by many names and through many familiar antinomies: local and global, micro and macro events. Even the most critical among us often proceed with our analysis as if such scales were the ready-made platforms of social life, rather than asking how, why, and to what effect are scalar distinctions forged in the first place. How do scalar distinctions help actors and analysts alike make sense of and navigate their social worlds? What do these distinctions reveal and what do they conceal? How are scales construed and what effects do they have on the way those who abide by them think and act? This pathbreaking volume attends to the practical labor of scale-making and the communicative practices this labor requires. From an ethnographic perspective, the authors demonstrate that scale is practice and process before it becomes product, whether in the work of projecting the commons, claiming access to the big picture, or scaling the seriousness of a crime. "How shall we fathom the world, bringing its varied scales into analytic perspective? The authors collected in this bold and subtle volume slow down the question, arguing that 'scale' is made, not born, and that 'perspectives' are semiotic accomplishments and not stable points of anchor." -STEFAN HELMREICH, Elting E. Morison Professor of Anthropology, MIT "Scale will be a fundamental book for thinking about scalar processes... It's engaging, readable chapters offer a range of theoretical considerations of how scales arise and work in a variety of social settings." -ROBERT OPPENHEIM, author of Kyongju Things: Assembling Place "This highly original volume sheds new light on language and scale... The authors show how the scalar aspects of language and the linguistic dimensions of scale work together to produce the social logic of extent." -ARJUN APPADURAI, Paulette Goddard Professor of Media, Culture and Communication, New York University "This groundbreaking collection of essays by leading linguistic anthropologists demonstrates the vital contribution of semiotics to the ongoing multidisciplinary theorizing of scale and scale-making." -MIYAKO INOUE, author of Vicarious Language: Gender and Linguistic Modernity in Japan E. SUMMERSON CARR is Associate Professor, School of Social Service Administration, University of Chicago. MICHAEL LEMPERT is Associate Professor of Anthropology, University of Michigan.